A modified slow sand filtration system of epikarst spring water in karst mountainous areas, China - Yuewen Zhao; Xiuyan Wang; Juan Yang; Changli Liu; Shuaiwei Wang (IWA Publishing, 2021)
Epikarst springs are commonly used for drinking water in karst mountainous areas, but they tend to bring health risks to residents because of their vulnerability. In this work, a modified slow sand filtration system (M-SSF) was established as a case study to purify and conserve the epikarst spring water. The outcomes indicate that the purification of M-SSF relies mainly on the adsorption and ion exchange of the filter medium (mixtures of heat-treated red clay and crushed limestone, MHRCCL) during the schmutzdecke juvenility, and on the schmutzdecke-formed food chain of pollutants → bacteria → protozoa after the schmutzdecke maturity. The closed water cellar lined with ceramic tiles could reduce the deterioration of epikarst spring water during storage. Via 16S rRNA sequencing, it was found that the high abundance of TM6_Dependentiae in purified epikarst spring water (PESW) suggested that the M-SSF system relies on the formation of a closed food chain to achieve effective water purification. The decrease of Pseudarcicella abundance in PESW indicated that M-SSF could effectively prevent the water quality from external influences represented by leeches. Besides, the 16S function prediction was used to qualitatively characterize microbial nitrogen metabolism, as well as organic matter degradation in water purification. HIGHLIGHTS The quality of epikarst spring water was significantly improved using the M-SSF.; TM6_Dependentiae indicated that the purification of M-SSF relies on the establishment of a closed food chain.; The M-SSF could prevent the purified epikarst spring water from being influenced by external pollution.;